Coming Out to Play: Privacy, Data Protection, Children’s Health, and COVID-19 Research - Beauvais, Michael J. S.; Knoppers, Bartha Maria (Frontiers in Genetics, 2021)
With the COVID-19 pandemic, we are at the apex of the collection, use, and disclosure of data about children. In this article, we contend that new ways of thinking about data protection issues with children in the health research context are overdue. We first outline the opportunities and challenges of children’s data. They are at once indispensable for the promotion of children’s rights and interests and yet pose risks to their well-being if improperly used. We then examine children’s rights to privacy and data protection under the Convention on the Rights of the Child (CRC) (1989) and the General Data Protection Regulation (GDPR) (2016), with specific reference to the best interests of the child standard. We contend that the lack of clear, child-specific provisions beyond those for social media websites means that a highly contextual approach must be taken to understanding the relationship of children’s privacy to health research. As such, we examine three specific issues for children and COVID-19 research: consent, data retention, and data protection impact assessments. Each of these three issues presents a delicate balancing exercise with few bright-line rules. As such, we conclude by calling for increased attention to the data protection needs of children in health research.